Lower limb muscles assessment in incomplete spinal cord injury patients by using magnetic resonance (MR) spectroscopy / Nur Syahfinaz Hidayah Rusli - Rusli, Nur Syahfinaz Hidayah (2022)
In Malaysia, spinal cord injury cases become epidemiological patterns among residents. Spinal cord injury is a signal disturbance moved by a bunch of nerves up and down between the human body and brain. This research study aimed to non invasively evaluate choline (CHO), creatine (Cr), and intramyocellular lipid (IMCL) metabolites in vastus lateralis, semitendinosus, and gluteus maximus muscles for incomplete spinal cord injury ASIA-AIS B, C, and D patients by using 1H-MRS, to compare the CHO, Cr, and IMCL metabolites among vastus lateralis, semitendinosus and gluteal maximus muscles, to measure the metabolites value changes before and after high-intensity FES cycling exercise among incomplete spinal cord injury ASIA AIS D patients, and to propose a metabolite as a potential indicator for assessing muscle activity in incomplete spinal cord injury ASIA-AIS B, C, and D patients. These metabolites were measured from the three critical muscles in 17 incomplete spinal cord injury ASIA-AIS B, C, and D patients. All subjects underwent 3 Tesla MRI (repetition time/echo time; TR/TE of 3500ms/100ms, field-of-view; FOV of 20cm, slice thickness of 6mm) and 1H-MRS (TR/TE of 2000ms/31ms, voxel size of 20mm x 20mm x 35mm) scans, then two incomplete spinal cord injury ASIA-AIS D subjects had functional electrical stimulation (FES) cycling sessions and followed by post MRI and 1H-MRS. The acquisition and analysis of CHO, Cr, and IMCL metabolite values for this research study could be performed on all 17 subjects without any exception. CHO metabolite in the semitendinosus and gluteus maximus muscles showed a statistically significant difference (p = 0.01) for strong legs. A significant difference was also detected for IMCL metabolite in the semitendinosus muscle (p = 0.01). Meanwhile, significant differences were detected for CHO and Cr metabolites in the vastus lateralis muscle (p = 0.02) for weak legs. For FES cycling exercise findings, only the IMCL value of semitendinosus showed a statistically significant difference between pre- and post-FES exercise (p = 0.01) in strong legs. In the meantime, only the Cr value of vastus lateralis showed a significant difference between pre- and post-FES exercise (p = 0.01) in weak legs. In conclusion, this study showed that 1H-MRS at 3T could non-invasively provide metabolic information regarding human skeletal muscles in incomplete spinal cord injury patients. Additionally, 1H-MRS detects metabolite changes before and after electrical stimulation on muscles. The result indicated that Cr metabolite could become a potential indicator to evaluate spinal cord injury patients' muscle activity.